The Validity of Ocular Health Testing in Tele-Optometric Eye Examinations in a Young Adult Population. - Sanghera, Navjit K.; Patel, Jaymeni; Wyles, Elizabeth; Yi Pang; Messner, Leonard V.; Morettin, Christina E. (Optometry & Visual Performance, 2023)
Background: The global COVID-19 pandemic has accelerated the transition from traditional care to telehealth in many facets of healthcare. Access to healthcare in otherwise remote locations, increased accessibility to appointments, and continuity of care are some of the more apparent advantages. This study aimed to compare anterior segment findings, posterior segment findings, and intraocular pressure (IOP) measurements between traditional in-person examination and tele-optometric examination. Methods: A cohort of 30 optometry students was recruited to complete two comprehensive eye examinations. A tele-optometric comprehensive eye exam was completed by an in-person technician via the DigitalOptometrics platform and video conferencing with an investigator optometrist. This was then followed by the gold standard inperson comprehensive eye exam by one of the investigator optometrists. Both eye examination methods included anterior and posterior segment evaluation, as well as IOP measurements. The teleoptometric examination used a 14-second Reichert slit lamp video recording to evaluate the anterior segment and the Eidon ultra-widefield retinal photographer to evaluate the posterior segment. DFE was completed with 90D biomicroscopy and binocular indirect ophthalmoscopy. Intraocular pressure (IOP) measurements were taken via non-contact tonometry (NCT) by an in-person technician for the telehealth exam, while the gold standard IOP measurement, Goldmann applanation tonometry (GAT) with Fluress, was taken by the investigator optometrist. Results: In chi-square statistical analysis, there was a statistically significant difference between telehealth and in-person anterior segment findings (χ2 =6.8 and p=0.009). Further analysis with Fisher’s exact test also showed a significant difference in anterior segment findings between telehealth and in-person (p=0.031). We could not perform chisquare statistical analysis on posterior segment findings because the data was not validated for chisquare analysis. In t-test statistical analysis, there was no statistically significant difference between telehealth and in-person IOP OD (p=0.166) and OS (p=0.076) measurements. The agreement in IOP between telehealth and in-person was also evaluated with Bland-Altman analysis, using the 95% limits of agreement, which corresponds to ±1.96* standard deviation of the differences between telehealth and in-person measurement. Conclusion: Based on our study design, we cannot conclusively state that telehealth is comparable to in-person exams when comparing anterior and posterior segment findings. When comparing IOP measurements, NCT in telehealth exams and GAT in in-person exams, the findings were comparable in accuracy. We are aware that there are trends in our results, but future studies should be designed specifically to address these gaps in analysis and limitations.